The importance of good governance in hospital payment reform - A case study from Ukraine - Karl Karol; Serhii Hryshchuk; Karolina Kalanj; Valentyn Parii (Elsevier, 2023)
In 2005, Ukraine embarked on hospital financing reforms that included the introduction of a Diagnosis Related Group (DRG) based payment system for acute inpatient care. The primary purpose of introducing activity-based funding was to provide incentives for hospitals to use their limited resources more efficiently.Following an extended period of preparation and planning during which technical assistance was provided by various development agencies, Ukraine took action to implement the DRG system at a national level in April 2018, through a World Bank project. While some progress was made, the execution of the reform faced challenges with the organisation and administration of the implementation process, and duplication of effort. The consequence of these shortcomings was that the newly introduced system was not capable of measuring inpatient DRG activity at a level of accuracy necessary for the determination of hospital performance and the subsequent calculation of payments.If the expected outcomes of DRG implementation in Ukraine are to be realised, stakeholders including both beneficiary agencies and development organisations, will need to improve program governance through better coordination of their activities towards a common goal.